Anchoring and Probability Weighting in Option Prices. Issue 6 (2nd February 2017) - DeLisle, R. Jared; Diavatopoulos, Dean; Fodor, Andy; Krieger, Kevin
Abstract : Cumulative prospect theory argues that the human decision‐making process tends to improperly weight unlikely events. Another behavioral phenomenon, anchoring bias, is the failure to update beliefs away from established anchor points. In this study, we find evidence that equity option market investors both anchor to prices and incorporate a probability weighting function similar to that proposed by cumulative prospect theory. The biases result in inefficient prices for put options when firms have relatively high or relatively low implied volatilities. This has implications for the cost of hedging long portfolios and long individual equity positions. © 2017 Wiley Periodicals, Inc. Jrl Fut Mark 37:614–638, 2017